Chemical thick copper deposition complex liquid and preparation method thereof

By adding specific proportions of copper sulfate, reducing agent and other components to the chemical copper depositing liquid, a chemical thick copper depositing composite liquid is prepared, which solves the problems of slow copper depositing speed and insufficient adhesion of traditional copper depositing liquid, and achieves high efficiency and uniformity copper layer deposition.

CN119465115APending Publication Date: 2025-02-18HUIZHOU JINSHENG NEW ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411469050.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The copper depositing speed of traditional chemical copper depositing liquid is slow, has low production efficiency, and is prone to insufficient adhesion between the electroless copper plating layer and the substrate, resulting in layered foaming.

Method used

Provide a chemically thick copper compound liquid containing copper sulfate, reducing agent, sodium hydroxide, complexing agent, stabilizer, accelerator, buffering agent and surfactant. It can be prepared by mixing and adding a specific proportion to improve the Solution of copper depositing speed and copper layer mass.

Benefits of technology

This chemically thick copper depositing composite liquid can significantly increase the copper depositing speed and form a uniform and dense copper layer, with good conductivity, adhesion and corrosion resistance, reduce layered foaming and improve production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005094207260000051
    Figure BDA0005094207260000051
  • Figure BDA0005094207260000061
    Figure BDA0005094207260000061
  • Figure BDA0005094207260000081
    Figure BDA0005094207260000081
Patent Text Reader

Abstract

The invention relates to the technical field of chemical copper deposition, in particular to chemical copper deposition complex liquid and a preparation method thereof.The chemical copper deposition complex liquid is prepared from, by weight, 1.0%-1.4% of copper sulfate, 3%-6% of a reducing agent, 8%-12% of sodium hydroxide, 5%-15% of a complexing agent, 0.1%-0.5% of a stabilizer, 0.3%-0.8% of an accelerator, 1%-3% of a buffering agent, 1%-2% of a surfactant and the balance water; the accelerator is obtained by mixing sodium thiosulfate, nickel sulfate and tungstate according to the weight part ratio of (3-5): (1-3): 2, and by adopting the formula, the copper deposition speed can be increased, and the copper deposition efficiency can be improved. The chemical thick copper deposition complex liquid can form a uniform and compact copper layer. The copper layer has good conductivity, adhesive force and corrosion resistance, and can meet the requirements for the quality of the copper layer in the fields of electronics, PCB manufacturing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical copper deposition, and more specifically, to a chemical thick copper deposition composite solution and a preparation method thereof. Background Art

[0002] Chemical copper deposition includes chemical thin copper deposition and chemical thick copper deposition. Among them, chemical thick copper deposition is a method of depositing a thicker copper layer on the surface of the substrate by chemical methods. The copper layer has good bearing capacity, wear resistance and conductivity, and low resistivity. It is often used in the manufacture of high-load electronic products, such as electricity, electronics, chemicals and automobile fields.

[0003] Chemical thick copper deposition is mainly achieved by reducing the copper ions in the chemical copper deposition solution to copper element. The copper plating layer prepared by the chemical copper deposition solution has good bonding strength, and the coating is uniform and tight. However, in the actual operation process, it is found that the copper deposition speed of the traditional chemical copper deposition solution is slow, the production efficiency is low, and it is easy to have the phenomenon of stratification and blistering due to insufficient adhesion between the chemical copper plating layer and the substrate. Summary of the invention

[0004] In order to solve the technical problems of slow deposition rate and unstable copper layer quality of traditional chemical deposition copper solution, the present application provides a chemical thick copper deposition composite solution and a preparation method thereof.

[0005] In the first aspect, the present application provides a chemical thick copper deposition composite solution, which adopts the following technical solution: A chemical thick copper deposition composite solution is prepared from the following raw materials in parts by weight: Copper sulfate 1.0-1.4% Reducing agent 3-6% Sodium hydroxide 8-12% Complexing agent 5-15% Stabilizer 0.1-0.5% Accelerator 0.3-0.8% Buffer 1-3% Surfactant 1-2% The rest is water; The accelerator is obtained by mixing sodium thiosulfate, nickel sulfate and tungstate in a weight ratio of (3-5): (1-3): 2.

[0006] By adopting the above technical scheme, a chemical thick copper deposition composite liquid is prepared, which can increase the copper deposition speed and copper deposition efficiency. The chemical thick copper deposition composite liquid can form a uniform and dense copper layer. The copper layer has good conductivity, adhesion and corrosion resistance, and can meet the requirements of the electronics, PCB manufacturing and other fields for the copper layer quality. At the same time, the chemical thick copper deposition composite liquid can greatly improve the adhesion between the chemical copper layer and the substrate, and it is not easy to produce the phenomenon of stratification bubbles during use.

[0007] Among them, in the process of chemical thick copper deposition, copper ions are reduced to metallic copper by a reducing agent, thereby forming a copper layer on the surface of the substrate. The concentration of copper sulfate directly affects the deposition rate and the quality of the copper layer. The copper deposition rate is guaranteed by adding an appropriate amount of copper sulfate. Too high or too low concentrations are not conducive to obtaining an ideal deposition effect. The reducing agent can reduce the copper ions in the solution to metallic copper, thereby forming a copper layer on the surface of the substrate. Sodium hydroxide is used to adjust the pH value of the solution. In the process of chemical thick copper deposition, an appropriate pH value helps to maintain the stability of the reaction and the solubility of copper ions, and accelerates the copper deposition rate. The complexing agent can form a stable complex with the copper ions to prevent the copper ions from precipitating prematurely in the solution and keep the copper deposition rate stable and uniform. The stabilizer can inhibit the generation of impurities in the solution and maintain the stability of the solution. The accelerator can accelerate the reduction reaction of copper ions and increase the deposition rate. The buffer can maintain the stability of the pH value of the solution to prevent the deposition effect from being affected by changes in the pH value during the reaction. The addition of the buffer helps to improve the stability and reliability of the chemical thick copper deposition process.

[0008] Among them, the accelerator is a mixture of sodium thiosulfate, nickel sulfate and tungsten, which can greatly speed up the copper deposition rate. Nickel sulfate is usually used as a catalyst or activator in the copper plating solution. It can promote the reduction reaction of copper ions, thereby increasing the copper plating rate. Tungstate is a commonly used accelerator with a depolarizing effect. It can reduce the cathode polarization, making it easier for copper ions to obtain electrons on the cathode surface and be reduced. Sodium thiosulfate plays a role in assisting reduction in the copper plating process. It can assist the reducing agent in reducing the copper ions in the solution to metallic copper, thereby achieving rapid deposition of copper on the substrate.

[0009] Surfactants can effectively reduce the surface tension of chemical thick copper plating composite solution, making it easier for the solution to wet the surface of the substrate, thereby improving the uniformity and quality of the coating. At the same time, during the chemical copper plating process, hydrogen embrittlement may occur due to the generation of hydrogen. The presence of surfactants helps to reduce the surface tension of the solution, making it easier for the generated hydrogen to detach from the surface of the precipitated copper layer, thereby reducing the possibility of hydrogen embrittlement.

[0010] Preferably, the complexing agent is obtained by mixing tartrate and nitrilotriacetate in a weight ratio of (6-8):3.

[0011] By adopting the above technical solution, tartrate and nitrilotriacetate can form a stable complex with copper ions together, which has higher stability and selectivity, thereby better controlling the release and deposition process of copper ions. By adjusting the ratio of tartrate and nitrilotriacetate, the stability of the complex and the release rate of copper ions can be affected, thereby adjusting the deposition rate of copper, while reducing pinholes, bubbles, and depressions, thereby obtaining a uniform and dense copper coating and improving the flatness of the copper coating.

[0012] Preferably, the nitrilotriacetate is prepared by the following method: A: Dissolve chloroacetic acid in water to obtain a chloroacetic acid solution, heat it to 40-50°C, add sodium hydroxide solution, adjust the pH to 6.5-7.5, and obtain a sodium chloroacetate solution; B: Heat the sodium chloroacetate solution to 50-60°C, add ammonium chloride, raise the temperature to 75-85°C, continue to drop sodium hydroxide solution under stirring, control the pH value of the system to 9-11, raise the temperature to 85-95°C, and keep the reaction for 2-3 hours; C: Cool the reaction solution in step B to 20-30°C, add hydrochloric acid, and stop adding hydrochloric acid when the pH value drops to 1-2, precipitate, and continue stirring for 15-20 minutes until it drops to room temperature, filter, rinse the solid, and dry to obtain nitrilotriacetate.

[0013] Preferably, the raw materials used to prepare the nitrilotriacetate are as follows in molar fractions: 1 part of chloroacetic acid Sodium hydroxide 0.9-1.1 parts Ammonium chloride 0.8-1 part 1.1-1.3 parts of hydrochloric acid.

[0014] The nitrilotriacetate complexing agent prepared by the above method has a significant effect on the chemical thick copper plating composite solution. The complexing agent can effectively stabilize the copper ions in the plating solution, prevent them from being precipitated prematurely, and ensure the stability of the copper plating process. The nitrogen atoms and oxygen atoms in the nitrilotriacetate form a stable complex with the copper ions, stabilize the concentration of the copper ions in the plating solution, make the chemical copper plating process more controllable, thereby adjusting the release rate of the copper ions and controlling the deposition rate, so as to obtain a uniform and dense coating.

[0015] The preparation process of nitrilotriacetate in the present application has clear steps and is easy to operate. Through reasonable temperature control and reaction time, the reaction is fully carried out, the reaction efficiency is improved, and the purity of nitrilotriacetate is guaranteed.

[0016] Preferably, the stabilizer is obtained by mixing 5-phenyltetrazolyl, nicotinamide and ethanol in a weight ratio of (3-6): (2-4): 5.

[0017] By adopting the above technical solution, the over-reduction of copper ions and the hydrogen evolution reaction in the copper plating process can be effectively suppressed, the stability of the plating solution can be maintained and the quality of the plating layer can be improved.

[0018] The role of 5-phenyltetrazolyl in the composite solution is to form stable copper complexes and compounds to prevent copper ion precipitation and oxidation, thereby enhancing the stability of the chemical copper plating solution. Nicotinamide may play an auxiliary stabilizing role in the copper plating solution. It can synergize with 5-phenyltetrazolyl to further improve the stability of the plating solution. Ethanol is mainly used as a solvent in the copper plating solution. It can dissolve and disperse stabilizer components such as 5-phenyltetrazolyl and nicotinamide, so that they are better dispersed in the plating solution and play a stabilizing role.

[0019] Preferably, the reducing agent includes at least one of formaldehyde, sodium hypophosphite, sodium borohydride, sodium formaldehyde bisulfite, dimethylamino borane and hydrazine.

[0020] By adopting the above technical solution and optimizing the type of reducing agent, the reduction rate of copper ions can be effectively increased and the copper deposition rate can be accelerated.

[0021] Preferably, the buffer comprises at least one of sodium bicarbonate, disodium hydrogen phosphate, sodium hydrogen citrate, sodium acetate and potassium dihydrogen phosphate.

[0022] By adopting the above technical solution, the type of buffer is optimized, so that the pH value of the chemical thick copper deposition composite solution remains unchanged, the copper plating speed is maintained, and the quality and uniformity of the coating are improved.

[0023] Preferably, the surfactant is obtained by mixing polyether polyol and polyethylene glycol in a weight ratio of (4-5):2.

[0024] As surfactants, polyether polyols and polyethylene glycol can significantly reduce the surface tension of the chemical thick copper plating composite liquid, help the liquid to better wet the surface of the substrate, and ensure a more uniform coating. They can accelerate the release of hydrogen, reduce the residence time of hydrogen in the coating, reduce pores and defects in the coating, and improve the density and brightness of the coating.

[0025] Preferably, it is prepared from the following raw materials in parts by weight: Copper sulfate 1.1% Reducing agent 5% Sodium hydroxide 11% Complexing agent 9% Stabilizer 0.3% Accelerator 0.6% Buffer 2.5% The rest is water; The accelerator is obtained by mixing sodium thiosulfate, nickel sulfate and tungstate in a weight ratio of 3:3:2.

[0026] By adopting the above technical solution, the dosage of raw materials for preparing chemical thick copper deposition composite liquid is further optimized, so that the copper deposition rate is faster, a more uniform and dense copper layer is formed, and the adhesion with the substrate layer is better.

[0027] In a second aspect, the present application provides a method for preparing a chemical thick copper deposition composite solution, which adopts the following technical scheme: A method for preparing a chemical thick copper deposition composite solution, comprising the following preparation steps: According to weight percentage, raw materials such as copper sulfate, reducing agent, sodium hydroxide, complexing agent, stabilizer, accelerator and buffer are mixed in proportion, and water is added to prepare a chemical thick copper deposition composite liquid.

[0028] By adopting the above technical solution, the prepared chemical thick copper deposition composite solution has a high deposition rate and a good and stable copper layer. The preparation method in the present application is simple and easy to control, which is conducive to ensuring the quality and stability of the composite solution.

[0029] In summary, this application has the following beneficial effects: 1. When the chemical thick copper composite solution in the present application is used for chemical plating, a uniform, dense, and highly adhesive copper plating layer can be obtained.

[0030] 2. The application adds a specific accelerator, which significantly increases the copper deposition rate, shortens the electroplating or chemical plating cycle, and improves production efficiency.

[0031] 3. The synergistic effect of the complexing agent and stabilizer helps to control the release rate and deposition rate of copper ions, prevent defects such as arching, pinholes, and pitting in the coating, and improve the quality of the coating.

[0032] 4. The addition of buffer and surfactant further improves the wettability between the coating and the substrate, which helps to obtain a more uniform and dense coating. DETAILED DESCRIPTION Example

[0033] Copper sulfate is anhydrous copper sulfate.

[0034] Polyether polyol was purchased from Shandong Shengteng Chemical Co., Ltd., model 330N.

[0035] Polyethylene glycol was purchased from Shandong Baihua Chemical Co., Ltd. with a CAS number of 25322-68-3.

[0036] Example 1 A chemical thick copper deposition composite solution is prepared by the following method: 10g of copper sulfate, 20g of reducing agent (formaldehyde), 80g of sodium hydroxide, 50g of complexing agent (potassium sodium tartrate), 1g of stabilizer (5-phenyltetrazolyl), 3g of accelerator (sodium thiosulfate), 10g of surfactant (polyether polyol) and 10g of buffer (sodium bicarbonate) are mixed in proportion, and 826g of water is added to prepare a chemical thick copper deposition composite liquid.

[0037] The accelerator is obtained by mixing sodium thiosulfate, nickel sulfate and tungstate (sodium tungstate) in a weight ratio of 3:1:2. The difference between Example 2-3 and Example 1 is that the types, amounts and parameters of some raw materials for preparing the chemical thick copper deposition composite solution are different. The specific differences are shown in Table 1: Table 1 Types, amounts and parameters of raw materials for preparing chemical thick copper composite solution in Examples 1-3 Example 4 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 1 is that: the complexing agent is obtained by mixing potassium tartrate and nitrilotriacetate in a weight ratio of 6:3.

[0038] Nitrilotriacetate was trisodium nitrilotriacetate, which was purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.

[0039] Example 5 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 1 is that: the complexing agent is obtained by mixing potassium tartrate and nitrilotriacetate in a weight ratio of 8:3.

[0040] Example 6 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 4 is that nitrilotriacetate is prepared by the following method: A: Dissolve 1 mol of chloroacetic acid in 250 g of water to obtain a chloroacetic acid solution, heat to 40°C, add 0.8 mol of sodium hydroxide, adjust the pH to 6.5, and obtain a sodium chloroacetate solution; B: Heat the sodium chloroacetate solution to 60°C, add 0.8 mol of ammonium chloride, raise the temperature to 75°C, continue to drop 0.1 mol of sodium hydroxide under stirring, control the pH value of the system to 9, raise the temperature to 85°C, and keep the reaction for 2 hours; C: Cool the reaction solution in step B to 20°C, add 1.2 mol of hydrochloric acid and sodium hydroxide, stop adding hydrochloric acid until the pH value drops to 1, precipitate, and continue stirring for 15 minutes until it drops to room temperature, filter, rinse the solid, and dry to obtain nitrilotriacetate Example 7 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 4 is that nitrilotriacetate is prepared by the following method: A: Dissolve 1 mol of chloroacetic acid in 300 g of water to obtain a chloroacetic acid solution, heat to 50°C, add 1 mol of sodium hydroxide, adjust the pH to 7, and obtain a sodium chloroacetate solution; B: Heat the sodium chloroacetate solution to 60°C, add 1 mol of ammonium chloride, raise the temperature to 85°C, continue to drop 0.1 mol of sodium hydroxide under stirring, control the pH value of the system to 11, raise the temperature to 95°C, and keep the reaction for 3 hours; C: Cool the reaction solution in step B to 30°C, add 1.3 mol of hydrochloric acid, and stop adding hydrochloric acid when the pH value drops to 2 to precipitate. Continue stirring for 20 minutes until the temperature drops to room temperature, filter, rinse the solid, and dry to obtain nitrilotriacetate.

[0041] Example 8 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 1 is that the stabilizer is obtained by mixing 5-phenyltetrazolyl, nicotinamide and ethanol in a weight ratio of 3:2:5.

[0042] Example 9 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 4 is that the stabilizer is obtained by mixing 5-phenyltetrazolyl, nicotinamide and ethanol in a weight ratio of 6:4:5.

[0043] Example 10 A chemical thick copper deposition composite solution, the difference between this embodiment and embodiment 6 is that the stabilizer is obtained by mixing 5-phenyltetrazolyl, nicotinamide and ethanol in a weight ratio of 6:4:5.

[0044] Embodiment 11 A chemical thick copper deposition composite liquid, the difference between this embodiment and embodiment 1 is that the surfactant is obtained by mixing polyether polyol and polyethylene glycol in a weight ratio of 4:2.

[0045] Example 12 A chemical thick copper deposition composite liquid, the difference between this embodiment and embodiment 4 is that the surfactant is obtained by mixing polyether polyol and polyethylene glycol in a weight ratio of 5:2.

[0046] Example 13 A chemical thick copper plating composite liquid, the difference between this embodiment and embodiment 8 is that the surfactant is obtained by mixing polyether polyol and polyethylene glycol in a weight ratio of 5:2.

[0047] Embodiment 14 A chemical thick copper deposition composite liquid. The difference between this embodiment and embodiment 1 is that 11g of copper sulfate, 50g of reducing agent (formaldehyde), 110g of sodium hydroxide, 90g of complexing agent (potassium sodium tartrate), 3g of stabilizer (5-phenyltetrazolyl), 6g of accelerator (sodium thiosulfate) and 25g of buffer (sodium bicarbonate) are mixed in proportion, and 705g of water is added to prepare a chemical thick copper deposition composite liquid.

[0048] Embodiment 15 A chemical thick copper deposition composite solution. The difference between this embodiment and embodiment 1 is that the complexing agent is nitrilotriacetate, and the types, amounts and experimental parameters of other raw materials are consistent with those of embodiment 1.

[0049] Comparative Example Comparative Example 1 A chemical thick copper deposition composite solution. The difference between this comparative example and Example 1 is that sodium chloride is used instead of sodium thiosulfate of equal mass, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0050] Comparative Example 2 A chemical thick copper deposition composite solution. The difference between this comparative example and Example 1 is that sodium chloride is used instead of nickel sulfate of equal mass, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0051] Comparative Example 3 A chemical thick copper deposition composite solution. The difference between this comparative example and Example 1 is that ammonium nitrate is used instead of tungstate of equal mass, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0052] Comparative Example 4 A chemical thick copper deposition composite solution. The difference between this comparative example and Example 1 is that the accelerator is omitted, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0053] Performance testing The chemical thick copper plating composite solutions prepared in Examples 1-4 and Comparative Examples 1-4 were tested for plating speed, appearance observation, copper plating layer adhesion stability, and plating solution stability.

[0054] Detection method / test method Determination of plating speed: Chemical copper plating is performed on a printed circuit board substrate with a size of 5cmx5cm. After 30 minutes of copper plating, the plating speed is determined by the mass method. The calculation formula is as follows: r=(△mX10 4 ) / (t*S*ρ*2) where: r is the average plating speed, μm / min; m is the mass difference between before and after plating, g; p is the density of copper, g / cm3 ; S is the surface area of ​​the board, cm 2 ; t is time, min.

[0055] Appearance observation: Use a scanning electron microscope (SEM) to observe whether the cross-section of the coating has arching, depression, etc.

[0056] Copper plating layer adhesion stability test: Chemical copper plating is performed on a printed circuit board substrate with a size of 5cmx5cm. The 100-grid test method is used. 3M 610 tape is used to tear and pull repeatedly, and the number of times it is torn when it falls off is counted.

[0057] Plating solution stability test: Since it takes a long time for the plating solution to decompose naturally, in order to shorten the experimental time, an accelerated method is generally used. The present invention uses a palladium chloride accelerated test to test the stability of the plating solution: add 15mL PdCl2 (0.18g / L) to 50mL of the plating solution, the temperature is 60°C, and record the plating solution decomposition time, that is, the time required to produce a large amount of red copper powder and hydrogen. The experimental data are shown in Table 2: Table 2 Experimental data of Examples 1-14 and Comparative Examples 1-4 It can be seen from Examples 1-14 and Comparative Examples 1-3 in combination with Table 2 that the chemical thick copper deposition composite solution prepared by the present application can better improve the stability of the chemical thick copper deposition composite solution, greatly improve the copper deposition speed, and there is no arching, depression, etc. on the surface of the copper plating layer. At the same time, the copper plating layer has good adhesion performance to the substrate.

[0058] By comparing Example 1 with Comparative Examples 1-4, the copper deposition speed in Comparative Examples 1-4 is lower than that in Example 1, especially the copper deposition speed in Comparative Example 4 is greatly reduced; arching and depressions occur in Comparative Examples 1-3; the adhesion performance in Comparative Examples 1-4 is not as good as that in Example 1, especially the adhesion performance in Comparative Example 4 is greatly reduced; the stability of the chemical thick copper deposition composite solution in Comparative Example 4 is poor. Through the experimental data of Example 1 and Comparative Examples 1-4, it can be known that the present application can improve the stability, copper deposition speed and adhesion performance of the chemical thick copper deposition composite solution by preparing an accelerator with sodium thiosulfate, nickel sulfate and tungstate in a specific ratio, while ensuring that there is no arching, depression and the like on the surface of the copper plating layer.

[0059] Compared with Example 4-5, Example 1 has a higher copper deposition rate, a higher stability of the chemical thick copper deposition composite solution of Example 4-5, and better adhesion performance of Example 4-5. Comparing Example 1 with Example 15, the copper deposition rate, stability and stability of the copper plating layer of Example 1 and Example 15 are substantially the same; From Examples 1, 4-5 and 15, it can be seen that in the present application, by mixing tartrate and nitrilotriacetate, the stability, copper deposition speed and adhesion performance of the chemical thick copper deposition composite solution can be improved.

[0060] Compared with Example 6-7, Example 4 shows that the copper deposition rate of Example 6-7 is improved, the stability of the chemical thick copper deposition composite solution of Example 6-7 is improved, and the adhesion performance of Example 6-7 is better, indicating that the nitrilotriacetate prepared by the method in this application can improve the stability, copper deposition rate and adhesion performance of the chemical thick copper deposition composite solution.

[0061] By comparing Example 1 with Example 8, the copper deposition rate of Example 8 is improved, the stability of the chemical thick copper deposition composite solution of Example 8 is improved, and the adhesion performance of Example 8 is better; Comparing Example 4 with Example 9, the copper deposition rate of Example 9 is improved, the stability of the chemical thick copper deposition composite solution of Example 9 is improved, and the adhesion performance of Example 9 is better; Compared with Example 6 and Example 10, the copper deposition rate of Example 10 is improved, the stability of the chemical thick copper deposition composite solution of Example 10 is improved, and the adhesion performance of Example 10 is better; It can be seen from Examples 1 and 8, Examples 4 and 9, and Examples 6 and 10 that the stability, copper deposition speed and adhesion performance of the chemical thick copper deposition composite solution can be improved by mixing 5-phenyltetrazolyl, nicotinamide and ethanol.

[0062] By comparing Example 1 with Example 11, the stability of the chemical thick copper deposition composite solution of Example 11 is improved, and the adhesion performance of Example 11 is better; Comparing Example 4 with Example 12, the stability of the chemical thick copper composite solution of Example 12 is improved, and the adhesion performance of Example 12 is better; Comparing Example 8 with Example 13, the chemical thick copper deposition composite solution of Example 13 has improved stability, and the adhesion performance of Example 13 is better; It can be seen from Examples 1 and 11, Examples 4 and 12, and Examples 6 and 13 that the stability and adhesion performance of the chemical thick copper deposition composite solution can be improved by mixing polyether polyol and polyethylene glycol.

[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A chemical thick copper deposition composite solution, characterized in that: Prepared from the following raw materials in parts by weight: Copper sulfate 1.0-1.4% Reducing agent 3-6% Sodium hydroxide 8-12% Complexing agent 5-15% Stabilizer 0.1-0.5% Accelerator 0.3-0.8% Buffer 1-3% Surfactant 1-2% The rest is water; The accelerator is obtained by mixing sodium thiosulfate, nickel sulfate and tungstate in a weight ratio of (3-5): (1-3):

2.

2. The chemical thick copper deposition composite solution according to claim 1, characterized in that: The complexing agent is obtained by mixing tartrate and nitrilotriacetate in a weight ratio of (6-8):

3.

3. A chemical thick copper deposition composite solution according to claim 2, characterized in that: The nitrilotriacetate is prepared by the following method: A: Dissolve chloroacetic acid in water to obtain a chloroacetic acid solution, heat it to 40-50°C, add sodium hydroxide, adjust the pH to 6.5-7.5, and obtain a sodium chloroacetate solution; B: Heat the sodium chloroacetate solution to 50-60°C, add ammonium chloride, raise the temperature to 75-85°C, continue to drop sodium hydroxide under stirring, control the pH value of the system to 9-11, raise the temperature to 85-95°C, and keep the reaction for 2-3 hours; C: Cool the reaction solution in step B to 20-30°C, add hydrochloric acid, and stop adding hydrochloric acid when the pH value drops to 1-2, precipitate, and continue stirring for 15-20 minutes until it drops to room temperature, filter, rinse the solid, and dry to obtain nitrilotriacetate.

4. The chemical thick copper deposition composite solution according to claim 3, characterized in that: The raw materials used to prepare the nitrilotriacetate are as follows in molar fractions: 1 part of chloroacetic acid Sodium hydroxide 0.9-1.1 parts Ammonium chloride 0.8-1 part 1.1-1.3 parts of hydrochloric acid.

5. The chemical thick copper deposition composite solution according to claim 1, characterized in that: The stabilizer is obtained by mixing 5-phenyltetrazolyl, nicotinamide and ethanol in a weight ratio of (3-6): (2-4):

5.

6. The chemical thick copper deposition composite solution according to claim 1, characterized in that: The surfactant is obtained by mixing polyether polyol and polyethylene glycol in a weight ratio of (4-5):

2.

7. The chemical thick copper deposition composite solution according to claim 1, characterized in that: The reducing agent includes at least one of formaldehyde, sodium hypophosphite, sodium borohydride, sodium formaldehyde bisulfite, dimethylamino borane and hydrazine.

8. The chemical thick copper deposition composite solution according to claim 1, characterized in that: The buffer comprises at least one of sodium bicarbonate, disodium hydrogen phosphate, sodium hydrogen citrate, sodium acetate and potassium dihydrogen phosphate.

9. The chemical thick copper deposition composite solution according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight: Copper sulfate 1.1% Reducing agent 5% Sodium hydroxide 11% Complexing agent 9% Stabilizer 0.3% Accelerator 0.6% Buffer 2.5% Surfactant 1% The rest is water; The accelerator is obtained by mixing sodium thiosulfate, nickel sulfate and tungstate in a weight ratio of 3:3:

2.

10. A method for preparing the chemical thick copper deposition composite solution according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: According to weight percentage, raw materials such as copper sulfate, reducing agent, sodium hydroxide, complexing agent, stabilizer, accelerator, surfactant and buffer are mixed in proportion, and water is added to prepare a chemical thick copper deposition composite liquid.